Merancang Pemasaran Digital dalam Meningkatkan Penjualan Tahu di UMKM Tahu Berkah Barokah Pada Desa Pekiringan Tegal - Riyanto, Riyanto; Faris, Ahmad Kamal Nur; Rifaldi, Martan Budi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2026)
Micro, Small, and Medium Enterprises (MSME) play a crucial role in Indonesia's economy, particularly in creating jobs and improving community welfare. However, MSMEs still face a number of challenges, especially in marketing and utilizing digital technology. One such example is Tahu Berkah Barokah, an MSME located in Pekiringan Village, Talang Subdistrict, Tegal Regency. This business specializes in tahu gambir and tahu putih (types of tofu), but still relies on conventional marketing methods and lacks a strong digital and legal business identity. Through a Community Service Program (PKM) carried out by a team from the Digital Technology University, a series of activities were implemented to enhance the competitiveness of the MSME. These activities included the creation of promotional banners, logo design as a visual business identity, registration of a Business Identification Number (NIB) for formal legality, development of a website as an online promotional medium, and the registration of the business location on Google Maps to make it easier for consumers to find. In addition, technical training was provided to the business owner to enable independent management of digital promotion. The results of this program show significant improvements in the business's image, visibility, and accessibility. The products have become more widely known both locally and online. Consumers can now easily access information about the business through the website and locate it via Google Maps. With an official NIB and appealing visual media, customer trust has also increased. This program demonstrates that collaboration between educational institutions and MSMEs can have a tangible positive impact in driving digital transformation and the development of micro enterprises in the digital era